2008
DOI: 10.1017/s0031182008000334
|View full text |Cite
|
Sign up to set email alerts
|

Structure in parasite component communities in wild rodents: predictability, stability, associations and interactions .... or pure randomness?

Abstract: SUMMARYExperimental data establish that interactions exist between species of intestinal helminths during concurrent infections in rodents, the strongest effects being mediated through the host's immune responses. Detecting immune-mediated relationships in wild rodent populations has been fraught with problems and published data do not support a major role for interactions in structuring helminth communities. Helminths in wild rodents show predictable patterns of seasonal, host age-dependent and spatial variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
74
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 115 publications
4
74
0
Order By: Relevance
“…A system containing more competing species will generally suffer from smaller sample sizes (the number of hosts carrying each kind of parasite), hindering quantitative inference. This may partly explain why studies reporting correlations have involved fewer species (Behnke 2008; Lello et al 2004). Pathogen association studies in general can be limited by the presence of hidden confounding factors, such as shared risks for pathogen acquisition, and spurious associations generated by the system’s nonlinear dynamics (Behnke et al 2005; Fenton et al 2010; Karvonen et al 2009; Lello et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A system containing more competing species will generally suffer from smaller sample sizes (the number of hosts carrying each kind of parasite), hindering quantitative inference. This may partly explain why studies reporting correlations have involved fewer species (Behnke 2008; Lello et al 2004). Pathogen association studies in general can be limited by the presence of hidden confounding factors, such as shared risks for pathogen acquisition, and spurious associations generated by the system’s nonlinear dynamics (Behnke et al 2005; Fenton et al 2010; Karvonen et al 2009; Lello et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Detecting this tradeoff only from correlations in natural carriage might be extremely difficult and potentially misleading (Fenton et al 2010; Holt 1984; Holt and Lawton 1993). Experiments in animal models, longitudinal coinfection studies augmented by immunological data, and interventions such as vaccines that target specific pathogens or strains could help to identify and, critically, quantify the strengths of direct and indirect effects (Behnke 2008; Bradley and Jackson 2008; Telfer et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…In some hosts, notably birds that harbour species-rich helminth communities, the evidence is indisputable, but in others such as fish and wild rodents characterized by relatively depauperate helminth communities, evidence in support of a role for interactions in structuring communities has been elusive (reviewed Behnke et al 2001). This contrasts markedly with laboratory studies where interactions between helminths have been clearly demonstrated and mostly assigned to interactions mediated through the immune response of the host (Behnke et al 2001 ;Behnke, 2008). The search for evidence of interactions among wild-caught hosts, has been hampered by a number of difficulties ; for example, the statistical analyses required to dissect out the evidence for interactions is complex (Haukisalmi and Henttonen, 1998 ;Howard et al 2001 ;Bottomley et al 2005), and there is a lack of support for any specific interaction between particular parasites being a consistent enough feature wherever both species of parasites co-occur with the host.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, climatic factors are known to influence the development of free-living stages of parasites and can affect survival, transmission and host infection (Haukisalmi & Henttonen, 1990;Behnke, 2008).…”
Section: Introductionmentioning
confidence: 99%